Aluminum Redistribution during the Preparation of Hierarchical Zeolites by Desilication. Issue 40 (11th August 2015) - Mitchell, Sharon; Milina, Maria; Verel, René; Hernández‐Rodríguez, Manuel; Pinar, Ana B.; McCusker, Lynne B.; Pérez‐Ramírez, Javier
Abstract A literature survey reveals a prominent reduction in the concentration of Brønsted acid sites in hierarchically organized zeolites with increasing mesoporous or external surface area independent of the framework type or synthesis route; this suggests a common fundamental explanation. To determine the cause, nature, and impact of the underlying changes in aluminum speciation, this study combines a multitechnique analysis that integrates basic characterization, a detailed synchrotron XRD and multiple‐quantum NMR spectroscopy assessment, and catalytic tests to correlate evolution of the properties with performance during successive steps in the preparation of hierarchical MFI‐type zeolites by desilication. The findings, subsequently generalized to FAU‐ and BEA‐type materials, identify the crucial impact of calcination on the protonic form, which is an integral step in the synthesis and regeneration of zeolite catalysts; on aluminum coordination; and the associated acidity trends.